Respostas
respondido por:
0
tirando o MMC dos denominadores fica (x-2)*(x-8)
x/(x-2)*(x-8) + x/(x-2)*(x-8)
x² - 8x / (x-8) (x-2) + x² -2x / (x-8)(x-2) = 1
simplificando = 2x² -10x / (x-8)(x-2)
2x²-10x/x²-8x-2x+16 = 1
2x²-10x=x²-10x+16 ------- x²=16 ----- x=+ ou - 4
espero ter ajudado !
x/(x-2)*(x-8) + x/(x-2)*(x-8)
x² - 8x / (x-8) (x-2) + x² -2x / (x-8)(x-2) = 1
simplificando = 2x² -10x / (x-8)(x-2)
2x²-10x/x²-8x-2x+16 = 1
2x²-10x=x²-10x+16 ------- x²=16 ----- x=+ ou - 4
espero ter ajudado !
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás